1992
DOI: 10.1148/radiology.183.2.1561357
|View full text |Cite
|
Sign up to set email alerts
|

Venous stenoses in patients who undergo hemodialysis: treatment with self-expandable endovascular stents.

Abstract: During a 32-month period, 25 modified self-expandable endovascular stents were placed in 20 hemodialysis access sites to treat 21 stenoses and four occlusions in 19 patients. All stenoses were initially dilated with a high-pressure balloon. The initial success rate was 90% (18 of 20 access sites). The stents were patent from 0 to 960 days (mean duration of follow-up, 309 days). At 2 years follow-up, the patency rates were as follows: primary, 25%; secondary, 34%; and tertiary, 42%. The morbidity rate associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…To avoid stent infection, stent placement should be delayed if there are signs of active infection in the patient. We did not administer prophylactic antibiotics during the procedure, and there were no cases of sepsis after deployment, such as were described by Quinn et al (29). There are no data to help prove that periprocedural application of heparin offers a substantial prolongation of acute patency after central venous stent implantation.…”
Section: Discussionmentioning
confidence: 93%
“…To avoid stent infection, stent placement should be delayed if there are signs of active infection in the patient. We did not administer prophylactic antibiotics during the procedure, and there were no cases of sepsis after deployment, such as were described by Quinn et al (29). There are no data to help prove that periprocedural application of heparin offers a substantial prolongation of acute patency after central venous stent implantation.…”
Section: Discussionmentioning
confidence: 93%
“…Zollikofer et al [8] treated 14 lesions with Wallstents, 12 of them still patent at 3-27 months (mean 19 months) at time of publication. At 2-year follow-up, Quinn et al [9] found patency rates as follows: primary, 25%; secondary, 34%; tertiary, 42%.…”
Section: Discussionmentioning
confidence: 99%
“…Although circumferential-tvpe stenosis frequently requires restenosis, the paten cy of vascular access is sufficiently long by repeated DA. Since the metallic stent technique has recently been applied to vascular access [17,18], insertion of the stent after DA might result in belter patency even if the stenotic lesion is the circumferential type. Schwab et al [19] reported that the early detection of lesions was of primary importance to ensure longer vascular access.…”
Section: Discussionmentioning
confidence: 99%